One new species of scorpion belonging to the genus Euscorpiops Vachon, 1980 from South China (Scorpiones: Euscorpiidae, Scorpiopinae) - Zhu, Ming-Sheng; Zhang, Lu; Lourenço, Wilson R. (Zootaxa, 2007)
A new species of scorpion, Euscorpiops yangi sp. nov. (Euscorpiidae) is described from Maguang County, Yunnan Province, China. The new species can be characterized by 18 external trichobothria (5 eb, 2 esb, 2 em, 4 est, 5 et) and 9 to 10 ventral trichobothria in the pedipalp patella; a narrow and elongated chela with a length vs width ratio equal to 3.4 on males and 3.3 on female; cheliceral movable finger with 5 basal teeth on ventral edge.